Effects of climate change on residential properties in Wemabod Estate, Ikeja, Lagos State, Nigeria - Peter, Nkolika J.; Okagbue, Hilary I.; Adelowo, Mofetoluwa G.; Samuel, Olugbemisola W.; Iroham, Chukwuemeka O.; Nto, Sunday E. (Frontiers in Sustainable Cities, 2024)
The real estate sector is significantly impacted by climate change, with effects ranging from increasing risks of flooding and wildfires to shifting demand for certain types of property.These impacts influence insurance prices, property maintenance procedures, and the overall desirability of specific homes. While climate risk is acknowledged in the financial industry, its implications for the commercial and residential real estate sector are mostly studied in developed countries, with limited research in developing countries like Nigeria. This study attempts to fill this gap by exploring the potential impacts of climate change on residential properties in Lagos State, Nigeria, using Wemabod properties as a case study. The methodology involved analyzing primary data collected from residents of Wemabod Estate, Ikeja, Lagos, Nigeria, with purposive sampling used to recruit 100 participants due to absence of reliable census data. Data analysis was conducted using mean rank, t-test, and analysis of variance (ANOVA). Findings showed that most respondents demonstrated a good level of awareness about climate change. Analysis revealed that residential characteristics such as age, gender, level of education, and knowledge level of climate risk significantly influenced residents' climate change coping and adaptation strategies, with notable mean differences in knowledge and perception based on these factors. The major perceived effects of climate change included extreme heat and flooding, followed by strong winds and irregular rainfall, leading to property impacts such as peeling paint, wall cracks, roof leakage, foundation shake, and burst pipes.These findings indicate that extreme heat and flooding are the primary climate change manifestations affecting residential properties in Lagos State. Property owners should implement measures to protect against these effects, regularly inspect and maintain their properties, consider climate risk in their insurance and maintenance plans, and stay informed about climate change impacts. This study underscores the need for further research on climate change's impact on real estate in developing countries to better understand and mitigate these risks.